2016
DOI: 10.1108/jbim-02-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

B2B technology adoption in customer driven supply chains

Abstract: Purpose – The purpose of this article is to develop and propose a comprehensive framework that identifies the factors that influence a company’s decision to adopt business to business (B2B) technologies. Design/methodology/approach – The authors review the literature regarding technology adoption from multiple disciplines including: Supply Chain Management, Logistics, Sociology, Information Systems, Marketing and Economics. A synthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 80 publications
0
45
1
Order By: Relevance
“…In organizations, multiple individuals, their individual service readiness and their perspectives on organizational service readiness will influence service adoption decisions. This shows how service readiness is interdependent between its levels and between individuals, and how service readiness and adoption are significantly more complex phenomena in an organizational context than in a consumer contextand possibly even more complex than technology adoption in an organizational context has so far been expected to be (Asare et al, 2016).…”
Section: Intention To Adopt Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In organizations, multiple individuals, their individual service readiness and their perspectives on organizational service readiness will influence service adoption decisions. This shows how service readiness is interdependent between its levels and between individuals, and how service readiness and adoption are significantly more complex phenomena in an organizational context than in a consumer contextand possibly even more complex than technology adoption in an organizational context has so far been expected to be (Asare et al, 2016).…”
Section: Intention To Adopt Adoptionmentioning
confidence: 99%
“…The concept of readiness is therefore suitable for a situation where the actual adoption of a technology or service is aspired to, but is not yet possible or timely. Most studies on technology readiness, like those on technology adoption in general (Asare et al, 2016), have focused on individuals, and only occasional studies have considered technology readiness among business customers (Vize et al, 2013). Some have focused on employees' readiness to adopt services for use in their work, such as Walczuch et al (2007), who found that optimism, innovativeness and insecurity significantly affected employees' perceptions of the usefulness and ease of use of software.…”
Section: Sourcementioning
confidence: 99%
“…What is more important to the company is whether the results of the technology being adopted are easy to demonstrate and make visible. Asare, Brashear-Alejandro, and Kang (2016) have found that observability is positively associated with an organization's intention to adopt B2B technologies.…”
Section: Adoption/use Of Social Media For International Marketing Purmentioning
confidence: 99%
“…The current study includes observability in the conceptual framework because social media use is highly observable, is transferable via WOM and recommendations from friends (Haridakis & Hanson, 2009) and can be stopped without additional cost (Valenzuela et al, 2009), so this factor may well be influential. The few studies that have examined the effect of observability on innovation adoption found mixed results, all indicating either a positive or a non-significant relationship (Chong and Pervan, 2007;Asare et al, 2016;Sanchez-Torres and Juarez-Acosta, 2019). In line with Rogers' model, it is expected that:…”
Section: H1 Social Media's Perceived Ease-of-use Will Positively Infmentioning
confidence: 99%
“…As originally illustrated by Robert Dahl (1957), coercive power is the ability of one actor to force someone else to do something that they would not otherwise do. From a business relationship perspective, power is often defined as one firm's ability to influence another firm (Asare et al, 2016;Rehme et al, 2016). In addition, it has been noted that power is relative, that it is not like money, for example, as it cannot be accumulated and no single firm has power in all situations (Pfeffer, 1981;Ireland, 2005).…”
Section: Sharing Total Value In Business Relationships-value Approprimentioning
confidence: 99%